2022
DOI: 10.1111/mcn.13375
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding and food‐group level inequality among Ethiopian children 6–23 months of age (2011–2019)

Abstract: Ensuring diet quality in the first 2 years of life is critical to preventing malnutrition and instilling healthy food preferences. Children's diet quality has changed little over time and inequalities by socioeconomic status, rural–urban residence, but also by food group may exist. Using data from the 2011, 2016 and 2019 demographic and health surveys (DHS), we estimated the prevalence and inequalities in the minimum diet diversity (MDD), minimum meal frequency (MMF) and minimum acceptable diet (MAD). We furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This highlights the need for a broader understanding of complementary feeding practices in the context of food and nutrition insecurity ( 36 , 37 ) . Similar negative associations between MAD and low socio-economic status were also found in others studies, which used Demographic and Health Surveys data, conducted in low- and middle-income countries ( 19 , 34 , 38 ) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This highlights the need for a broader understanding of complementary feeding practices in the context of food and nutrition insecurity ( 36 , 37 ) . Similar negative associations between MAD and low socio-economic status were also found in others studies, which used Demographic and Health Surveys data, conducted in low- and middle-income countries ( 19 , 34 , 38 ) .…”
Section: Discussionsupporting
confidence: 88%
“…This highlights the need for a broader understanding of complementary feeding practices in the context of food and nutrition insecurity (36,37) . Similar negative associations between MAD and low socio-economic status were also found in others studies, which used Demographic and Health Surveys data, conducted in low-and middleincome countries (19,34,38) . We observed a reduction in the percentage of children aged 6-24 months who consumed sweetened beverages and UPF, independently of the extreme poverty quintiles.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In line with earlier quantitative studies conducted in Ethiopia, our qualitative study indicated that milk consumption among children was relatively low or infrequent despite widespread cattle ownership [ 32 ]. However, this study revealed that the true nutrient intake from milk may be even lower than expected because, in this study setting at least, milk was given to children after extracting butter, and often are diluting the skim milk with water.…”
Section: Discussionsupporting
confidence: 85%
“…Altogether, this suggests the need to ensure the safety of complementary foods through the implementation of baby WASH interventions (Waller et al, 2020). First, inequalities in diet, access to health care, and WASH need to be addressed (Girma et al, 2021;Tizazu et al, 2022). According to the studies by Girma et al (2021) and Tizazu et al (2022), rural households and those from lower socioeconomic status were those that could not afford to consume nutrient-dense food groups, access essential health-and WASH services; hence, were the most affected by various forms of malnutrition.…”
Section: Water Sanitation and Hygiene (Wash)mentioning
confidence: 99%